Bilateral Choroidal Metastases as Presentation of Dissemination of Cutaneous Malignant Melanoma - S. Fernandez-Perez; O. Ruiz-Moreno; V. Pueyo; G. de la Mata; L. Pablo (Case Reports in Ophthalmological Medicine)
Case Report. A 47-year-old man presented with blurred vision in the right eye. Ophthalmoscopic examination showed several placoid, pigmented lesions in the posterior pole and midperiphery of the retina of both eyes. Results. Patient referred a cutaneous malignant melanoma on the back skin removed 6 years ago. A systemic workup revealed multiple metastases in liver and spleen. After an exhaustive study we concluded that it was a dissemination of a cutaneous malignant melanoma with bilateral choroidal metastases, liver and spleen metastases. The patient obtained clinical ocular improvement after palliative chemotherapy, although he died in the following months. Pathological examination of the lesions confirmed the diagnosis of choroidal metastases from a malignant cutaneous melanoma. Conclusions. Monitoring patients who have had cutaneous malignant melanoma is very important, since melanoma metastases may occur even many years after the diagnosis of the primary tumor. Choroidal metastases from cutaneous melanoma are uncommon but we should be aware because their appearance worsens prognosis.